2020
DOI: 10.2147/jhc.s258930
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prognostic Significance of Serum Insulin-Like Growth Factor-1 in Hepatocellular Cancer Patients: A Validation Study</p>

Abstract: Background The Child–Turcotte–Pugh score (CTP) is the most commonly used tool to assess hepatic reserve and predict survival in hepatocellular cancer (HCC). The CTP stratification accuracy has been questioned and attempts have been made to improve the objectivity of the system. Serum insulin-like growth factor-1 (IGF-1)-CTP has been proposed to improve CTP prognostic accuracy. We aimed to validate the IGF-CTP score in our patient population. Patients and Methods A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Subsequently, we prospectively validated a revised CTP scoring system by replacing the subjective clinical assessment of ascites and encephalopathy in the CTP score with objectively quantified plasma IGF-1 levels to create new IGF/CTP score classes (IGF/CTP-A, -B, and -C, with A indicating low risk, B indicating intermediate risk, and C indicating high risk). This new scoring system was significantly associated with HCC survival prediction [21][22][23]. In addition, our results showed that a significant number of patients in the old CTP class A were reassigned as IGF/ CTP-B or -C and had significantly poorer survival than did those in IGF/CTP-A, proving the usefulness of the IGF/ CTP composite score to refine the CTP scoring system's prognostic accuracy.…”
Section: Introductionmentioning
confidence: 56%
“…Subsequently, we prospectively validated a revised CTP scoring system by replacing the subjective clinical assessment of ascites and encephalopathy in the CTP score with objectively quantified plasma IGF-1 levels to create new IGF/CTP score classes (IGF/CTP-A, -B, and -C, with A indicating low risk, B indicating intermediate risk, and C indicating high risk). This new scoring system was significantly associated with HCC survival prediction [21][22][23]. In addition, our results showed that a significant number of patients in the old CTP class A were reassigned as IGF/ CTP-B or -C and had significantly poorer survival than did those in IGF/CTP-A, proving the usefulness of the IGF/ CTP composite score to refine the CTP scoring system's prognostic accuracy.…”
Section: Introductionmentioning
confidence: 56%
“…Finally, in a more recent cohort in which many patients (42.8%) had underlying HBV as the primary etiology of the tumor, 51.8% of the patients were reclassified; however, IGF-CTP scores did not predict OS better than the original CTP scores. 9 Collectively, the patients in these cohorts had heterogeneous demographics, underlying risk factors, HCC stages, and treatments that may have independently affected their survival. More importantly, these studies were retrospective and were not powered to detect significant differences in patient risk stratification and in predicting OS with the IGF-CTP and the original CTP scoring systems.…”
Section: Discussionmentioning
confidence: 99%
“…8 This new scoring system, the IGF-CTP classification system, was validated as a means to assess hepatic reserve in different cohorts of patients with HCC and showed promising but inconclusive results regarding the prediction of OS and patient stratification compared with the CTP scoring system. 5,[9][10][11][12] Notably, these studies were not randomized and had relatively few patients; therefore, they were underpowered to test the superiority of IGF-CTP.…”
Section: Introductionmentioning
confidence: 99%
“…A correlation was found between the intensity of cirrhosis and the onset of HCC and low serum IGF-1 concentration. 46 , 47 …”
Section: Classification Of Hccmentioning
confidence: 99%